Sexual Dysfunction in Cervical Cancer Survivors: A Scoping Review - Neha Mishra; Nilanchali Singh; Mohini Sachdeva; Prafull Ghatage (Mary Ann Liebert, 2021)
Sexual function in cervical cancer survivors declines significantly after treatments irrespective of the modality used. Only a few studies have looked at their psychosexual needs, perception, and acceptance of psychosexual support. This review summarizes findings of current qualitative as well as quantitative studies to understand the plight of cervical cancer survivors regarding sexual dysfunction and the management issues. The effect of gynecologic cancers on sexuality depends on multiple factors such as psychosexual factors, biologic factors, and age. Younger patients have poorer outcomes with a more pronounced impact on sexual well-being. Radicality of surgery has direct correlation with sexual dysfunction. Low or no sexual interest, lack of lubrication, dyspareunia, and reduced vaginal caliber are frequently found. For too long, researchers have focused on defining the prevalence and types of sexual problems after various cancer treatments. The area that continues to be neglected is the evaluation of effective interventions to prevent or treat cancer-related sexual dysfunction. In particular, mental health and medical specialists need to collaborate to create cost-effective treatment programs. Collaborative intervention with gynecologists, sexologists, radiotherapists, and nursing staff would be beneficial to optimize the sexual wellness of cancer survivors and their spouses.